Impact of unfavorable factors on outcomes among inoperable stage II-IV Nonsmall cell lung cancer patients treated with proton therapy. (4th March 2019) - Zhu, He J.; Nichols, Romaine C.; Henderson, Randal H.; Morris, Christopher G.; Flampouri, Stella; Pham, Dat C.; Klassen, Christopher L.; Seeram, Vandana; Cury, James D.; Jones, Lisa; McGee, Lisa; Hoppe, Bradford S.
Abstract: Purpose: To investigate the impact of unfavorable risk factors among patients with locally advanced nonsmall cell lung cancer (LA-NSCLC) treated with proton therapy (PT). Material and Methods: From May 2008 through July 2015, 90 consecutive patients with unresectable stage II-IV (oligometastatic) NSCLC were treated with PT. Unfavorable factors including age ≥80 years, stage IV, weight loss >10% in 3 months, performance status (PS) ≥2, FEV1 < 1.0 or O2 dependency, prior lung cancer, prior lung surgery, prior 2nd cancer in the past 3 years, and prior chest irradiation were evaluated. All patients received standard fractionation of 1.8–2 Gy(RBE) (median dose, 70 Gy[RBE]). Overall survival (OS) and progression-free survival (PFS) were calculated with the Kaplan-Meier method. The impact of unfavorable factors was analyzed in Cox regression models. Results: Twenty-six percent were favorable-risk, while 42%, 22%, and 10% had 1-, 2-, or ≥3 unfavorable factors. The 2-year OS was 52% and 45% ( p  = .8522), and 2-year PFS was 21% and 44% ( p  = .0207), for favorable and unfavorable risk patients, respectively. Among patients with stage III-IV, only PS ≥2 adversely impacted OS ( p = .0015). Conclusion: Most patients treated with PT for LA-NSCLC have unfavorable risk factors. These patients had similar outcomes to favorable-risk patients. Enrollment in future clinical trials may improve if eligibility is less restrictive.